2009
DOI: 10.1093/humrep/dep007
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and reproductive aging

Abstract: BACKGROUNDRate of reproductive aging may be related to rate of biological aging. Thus, indicators of aging, such as short telomere length, may be more frequent in women with a history suggestive of premature reproductive senescence.METHODSTelomere-specific quantitative PCR was used to assess telomere length in two groups of women with evidence of reproductive aging: (i) patients with idiopathic premature ovarian failure (POF, N = 34) and (ii) women with a history of recurrent miscarriage (RM, N = 95); and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 47 publications
5
69
0
3
Order By: Relevance
“…For this reason, these women had less ovarian follicles, aged ovaries and also long leukocyte telomeres. Increased telomere length in premature ovarian failure (POF) reported in the study of Hanna et al, similar to the study conducted by Dorland et al, was explained by longer telomeres in blood, reflecting fewer mitotic divisions in the initial germ cell pool, which could also explain a smaller follicular pool and early menopause in POF patients (Hanna et al, 2009). …”
Section: Depletion Of Ovarian Folliclessupporting
confidence: 60%
“…For this reason, these women had less ovarian follicles, aged ovaries and also long leukocyte telomeres. Increased telomere length in premature ovarian failure (POF) reported in the study of Hanna et al, similar to the study conducted by Dorland et al, was explained by longer telomeres in blood, reflecting fewer mitotic divisions in the initial germ cell pool, which could also explain a smaller follicular pool and early menopause in POF patients (Hanna et al, 2009). …”
Section: Depletion Of Ovarian Folliclessupporting
confidence: 60%
“…Interestingly, some studies have revealed that patients with recurrent spontaneous abortions had shorter TLs. However, other studies reported that the TLs of premature ovarian failure patients were longer that those of the control group (Hanna et al 2009). Additional studies reported that infertile women undergoing COH treatment had significantly longer telomeres than healthy women of a similar age (Dorland et al 1998).…”
Section: Discussionmentioning
confidence: 89%
“…18 And 95 women with a history of recurrent miscarriage had shorter average telomere length than 108 women from the general population. 22 Yet these epidemiologic investigations have also not been entirely consistent, since longer average leukocyte telomere length was observed in women experiencing premature ovarian failure compared with women from the general population, 22 and poorly responding IVF patients older than 34 years with unexplained fertility disorder had longer lymphocyte telomere length compared with similarly aged fertile women. 21 Previous authors have explained the seeming inconsistencies in findings by attributing greater relative importance to one of the multiple factors that affect the reproductive lifespan by influencing the number of primordial follicles: the number of primordial germ cells, their mitotic ability, and the activity of telomerase.…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous authors have explained the seeming inconsistencies in findings by attributing greater relative importance to one of the multiple factors that affect the reproductive lifespan by influencing the number of primordial follicles: the number of primordial germ cells, their mitotic ability, and the activity of telomerase. 22 For example, it has been postulated that women with an unexplained fertility disorder may have a longer cell cycle, leading to fewer cell divisions and therefore fewer reductions in telomere length and a smaller pool of follicles. 21 We do not dispute the plausibility of such scenarios, in which the relationship between telomere length and menopausal age would depend on a woman's fertility status and reason for infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation